Effects of 12-week High-Intensity Functional Training on physical fitness in Wushu athletes - Wang, Xinzhi; Soh, Kim Geok; Ma, Shuzhen; Xu, Fan; Zhang, Dong; Lei, Qian (Elsevier, 2026)
High-intensity functional training (HIFT) has gained prominence in athletic preparation; however, its specific efficacy in male Wushu athletes remains undetermined. In this randomized controlled trial, sixty athletes were randomly assigned to an experimental group (EG) or a control group (CG). The EG undertook a structured 12-week HIFT intervention, comprising three 60-min sessions per week. The CG performed matched standard conditioning of equal duration and frequency, targeting 60%–70% HRmax. Physical fitness outcomes were assessed at baseline, week 6, and week 12, and data were analyzed using generalized estimating equations, with effect sizes expressed as model-based Cohen's d. Compared to standard training, HIFT elicited significantly greater improvements in push-ups, standing long jump, rope jumping, and 30 m sprint performance (all p < 0.05, d = 0.57–0.93). The results demonstrate that HIFT can effectively enhance key performance-related fitness components in Wushu athletes, suggesting its utility as a conditioning strategy for combat sports.